PENDAMPINGAN OPTIMALISASI MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI PADA USAHA JASA ANGKUTAN BARANG JASA ANGKUT GO - Kharis Hudaiby Hanif; Jalalludin Akbar; Ahmad Harits Fahriansyah; Adi Saputra; Muhammad Ilham Maulana; Muhammad Tegar Pratama Nurali (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
Abstract: This community service program aims to optimize the use of social media as a digital promotion strategy for a local freight transportation business, Jasa Angkut GO. The program was implemented through a participatory assistance approach involving business owners and operational teams. The stages of activities included situation analysis, planning promotional strategies, assistance in creating promotional content, and mentoring in managing social media platforms such as WhatsApp, Instagram, TikTok, and Facebook. The results of the program indicate an improvement in business visibility, expansion of market reach, and faster communication between service providers and customers. In addition, the assistance process contributed to increasing partners’ awareness and capacity in utilizing social media more systematically and sustainably for business promotion. This program demonstrates that structured social media assistance can serve as an effective strategy to strengthen the competitiveness of small-scale freight transportation services in the digital era